Preparation method of aluminum nitride thin film

By using large volume flow ratio nitrogen and argon gas phase deposition and hydrolysis treatment in the preparation of aluminum nitride films, a uniform floc structure is formed, which solves the uniformity and film quality of aluminum nitride films, and improves the quality of the epitaxial layer and Thickness control.

CN118712057BActive Publication Date: 2024-12-31DONGGUAN ZHONGTU SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411187537.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-31
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing aluminum nitride film preparation process leads to poor uniformity and film quality of aluminum nitride films, which limits the reduction of epitaxial layer thickness and the control of lattice defects.

Method used

The gas phase deposition is carried out using a mixed gas of nitrogen and argon gas of large volume flow ratio to form a uniform floc structure. It combines hydrolysis treatment and surface modification treatment to remove lattice defects and impurities, and improve the flatness and uniformity of the aluminum nitride film. .

Benefits of technology

The uniformity and film layer quality of the aluminum nitride film are significantly improved, the growth dislocation and stress of the epitaxial layer are reduced, and the quality and thickness control accuracy of the epitaxial layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118712057B_ABST
    Figure CN118712057B_ABST
Patent Text Reader

Abstract

The disclosed embodiment provides a method for preparing an aluminum nitride film, comprising: preparing an aluminum nitride film semi-finished product on a substrate; continuing to deposit aluminum nitride on the semi-finished product using a first physical vapor deposition process to obtain an aluminum nitride film finished product; the volume flow ratio of nitrogen and argon in the first physical vapor deposition process is greater than 95:5. Under the condition of an extremely high nitrogen flow percentage, the sputtered aluminum atoms form tiny grains with nitrogen (nitrogen atoms) before being deposited on the surface of the aluminum nitride film, and the tiny grains are deposited on the surface of the aluminum nitride film in a uniform and refined deposition manner, so that the surface of the aluminum nitride film presents a uniform flocculent structure. The aforementioned flocculent structure can better adapt to the growth of the epitaxial layer, facilitate epitaxial recrystallization, reduce epitaxial layer growth dislocations and stresses, and improve epitaxial quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of semiconductor process technology, and in particular to a method for preparing an aluminum nitride film. Background Art

[0002] Driven by the demand for semiconductor devices to develop in the direction of smaller structures, the thickness index of the epitaxial layer in the process of semiconductor device preparation is getting smaller and smaller. Because the uniformity and film quality of the aluminum nitride film buffer layer directly affect the defect control in the process of epitaxial layer generation, the reduction of the thickness index of the epitaxial layer also puts forward higher index requirements for the surface quality of the aluminum nitride film as a buffer layer. At present, the thickness of aluminum nitride film prepared by magnetron sputtering process can reach about 15.0nm, but the internal range is still 2.0-3.0nm. By observing the surface of aluminum nitride film under microscopic magnification, it presents a flaky grain structure. The area where lattice defects appear in the epitaxial layer generated on this surface structure is higher, which limits the reduction of the thickness of the epitaxial layer. Summary of the invention

[0003] In order to solve the problem of poor uniformity and film quality of aluminum nitride thin films caused by the existing aluminum nitride thin film preparation process, the embodiments of the present disclosure provide a new method for preparing aluminum nitride thin films.

[0004] In a first aspect, an embodiment of the present disclosure provides a method for preparing an aluminum nitride thin film, comprising:

[0005] preparing a semi-finished aluminum nitride film on a substrate;

[0006] A first physical vapor deposition process is used to continue depositing aluminum nitride on the semi-finished product to obtain a finished aluminum nitride film; in the first physical vapor deposition process, the volume flow ratio of nitrogen to argon is greater than 95:5.

[0007] Optionally, the volume ratio of nitrogen to argon in the first physical vapor deposition process is greater than 95:5, specifically:

[0008] The flow volume ratio of nitrogen gas to argon gas in the first physical vapor deposition process is between 95:5 and 99:1.

[0009] Optionally, the step of continuing to deposit aluminum nitride on the semi-finished product by using the first physical vapor deposition process includes:

[0010] The first physical vapor deposition process is controlled to last for 10-20 seconds to achieve continuous deposition of aluminum nitride on the semi-finished product.

[0011] Optionally, the step of preparing a semi-finished aluminum nitride film on a substrate comprises:

[0012] Depositing aluminum nitride on the substrate to obtain an aluminum nitride film with a first target thickness; the first target thickness is 5.0-30.0 nm;

[0013] Performing a defect hydrolysis treatment on an aluminum nitride film of a first target thickness, and performing a cleaning treatment after the hydrolysis treatment; wherein the hydrolysis treatment is used to remove lattice defects in the aluminum nitride film, and the cleaning treatment is used to remove a hydrolysis solution and / or a hydrolysis solute remaining on the aluminum nitride film;

[0014] A second physical vapor deposition process is used to continue depositing aluminum nitride on the cleaned aluminum nitride film to obtain the semi-finished product.

[0015] Optionally, the aluminum nitride film having the first target thickness is subjected to a hydrolysis treatment, comprising:

[0016] At a first target temperature, using a saturated carbonic acid solution to hydrolyze an aluminum nitride film of a first target thickness for 600-800 seconds, wherein the first target temperature is between 20° C. and 30° C.;

[0017] The cleaning treatment after the hydrolysis treatment includes: performing oxygen isolation and drying treatment after the hydrolysis treatment.

[0018] Optionally, the volume flow ratio of nitrogen and argon in the second physical vapor deposition process is 1:1.

[0019] Optionally, before depositing aluminum nitride on the substrate to obtain an aluminum nitride film of the first target thickness, the method further includes: performing surface modification treatment on the substrate to convert surface dangling bonds of the substrate used for depositing the aluminum nitride film into amino bonds;

[0020] The method of depositing aluminum nitride on a substrate to obtain an aluminum nitride film of a first target thickness comprises: depositing aluminum nitride on a modified substrate to obtain an aluminum nitride film of a first target thickness.

[0021] Optionally, the surface modification treatment of the substrate includes:

[0022] The substrate is cleaned for 750-900 seconds at the second target temperature using an RCA solution to modify the surface of the substrate; the ratio of ammonia water, hydrogen peroxide and deionized water in the RCA solution is 2:3:5, and the second target temperature is between 80-95° C.;

[0023] The surface-modified substrate is rinsed and oxygen-isolated and dried;

[0024] The step of depositing aluminum nitride on the modified substrate comprises: depositing aluminum nitride on the substrate that has been subjected to oxygen isolation and drying treatment.

[0025] Optionally, the step of depositing aluminum nitride on the modified substrate to obtain an aluminum nitride film having a first target thickness includes:

[0026] A third physical vapor deposition process is used to deposit aluminum nitride crystal nuclei with discrete uniform distribution on the modified substrate, and a two-dimensional layered structure is grown on the basis of the aluminum nitride crystal nuclei to obtain an aluminum nitride film with a second target thickness, wherein the second target thickness is 3.0-5.0 nm;

[0027] Using a second physical vapor deposition process to continue depositing aluminum nitride on the aluminum nitride film of the second target thickness, to obtain an aluminum nitride film of the first target thickness;

[0028] Among them, the volume flow ratio of nitrogen and argon in the third physical vapor deposition process is 1:1; the gas flow rate per unit time in the third physical vapor deposition process is smaller than the gas flow rate per unit time in the second physical vapor deposition process, and the sputtering power per unit area of ​​the aluminum target in the third physical vapor deposition process is greater than the sputtering power per unit area of ​​the aluminum target in the second physical vapor deposition process.

[0029] Optionally, in the process of depositing aluminum nitride using the second physical vapor deposition process, the temperature of the substrate pedestal is controlled to be a first target temperature;

[0030] During aluminum nitride deposition using the third physical vapor deposition process, the temperature of the substrate base is controlled to be at a second target temperature; the first target temperature is lower than the second target temperature.

[0031] According to the solution of the embodiment of the present disclosure, after obtaining the semi-finished aluminum nitride film, a nitrogen and argon mixed gas with a large volume flow ratio is injected into the vapor deposition equipment to continue vapor deposition on the surface of the aluminum nitride film. Under the condition of an extremely high nitrogen flow percentage, the sputtered aluminum atoms form small grains with nitrogen (nitrogen atoms) before being deposited on the surface of the aluminum nitride film. The small grains are deposited on the surface of the aluminum nitride film in a uniform and refined deposition manner, so that the surface of the aluminum nitride film presents a uniform flocculent structure. The aforementioned flocculent structure can better adapt to the growth of the epitaxial layer, facilitate epitaxial recrystallization, reduce epitaxial layer growth dislocations and stresses, and improve epitaxial quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work, including:

[0034] Figure 1 is a flow chart of a method for preparing an aluminum nitride film provided in an embodiment of the present disclosure;

[0035] Figure 2 It is a microscopic schematic diagram of the surface of the aluminum nitride film formed in the prior art solution;

[0036] Figure 3 is a microscopic schematic diagram of the surface of an aluminum nitride film formed by the process of the embodiment of the present disclosure;

[0037] Figure 4 This is a thickness simulation diagram obtained by measuring the aluminum nitride film formed by the process of this embodiment using an ellipsometer;

[0038] Figure 5 It is a thickness simulation diagram obtained by measuring the aluminum nitride film formed by the existing process based on the ellipsometry spectrometer;

[0039] Figure 6 This is a distribution diagram of diffraction light intensity in the lattice direction of the aluminum nitride film 002 formed based on the process of the disclosed embodiment;

[0040] Figure 7 is a flow chart of a method for preparing a semi-finished aluminum nitride film provided by some embodiments;

[0041] Figure 8 It is a flow chart of the method for preparing aluminum nitride film provided in some embodiments of the present disclosure. DETAILED DESCRIPTION

[0042] Embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although certain embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be construed as being limited to the embodiments described herein, which are instead provided for a more thorough and complete understanding of the present disclosure. It should be understood that the drawings and embodiments of the present disclosure are only for exemplary purposes and are not intended to limit the scope of protection of the present disclosure.

[0043] The term "including" and its variations used in this document are open inclusions, that is, "including but not limited to". The term "based on" means "based at least in part on". The term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments". Relevant definitions of other terms will be given in the description below. It should be noted that the concepts of "first", "second", etc. mentioned in this disclosure are only used to distinguish different devices, modules or units, and are not used to limit the order or interdependence of the functions performed by these devices, modules or units.

[0044] The disclosed embodiment provides a novel method for preparing an aluminum nitride film, which improves the surface flatness of the aluminum nitride film by adjusting the ratio of reactants in the preparation process (especially in the later stage of preparation).

[0045] Figure 1 FIG. 1 is a flow chart of a method for preparing an aluminum nitride film according to an embodiment of the present disclosure. Figure 1 As shown, the method for preparing the aluminum nitride film provided in the embodiment of the present disclosure includes S110-S120.

[0046] S110: Preparing a semi-finished aluminum nitride film on a substrate.

[0047] In the embodiments of the present disclosure, the substrate is a base for supporting various layered structures in the entire semiconductor manufacturing process. The substrate can be a crystal of various material types. For example, the substrate can be a sapphire substrate, a silicon substrate, etc., which is not limited in the embodiments of the present disclosure.

[0048] In a specific implementation, an aluminum nitride thin film semi-finished product can be prepared on a substrate using an existing preparation process. For example, various physical vapor deposition processes used in the prior art (such as a direct current physical vapor deposition process, a radio frequency physical vapor deposition process, a magnetron sputtering deposition process, and an ionized physical vapor deposition process). In other words, a corresponding type of physical vapor deposition equipment can be used to prepare an aluminum nitride thin film to obtain an aluminum nitride thin film semi-finished product.

[0049] In order to make the structure of the entire embodiment clear, how to prepare aluminum nitride film semi-finished products in some embodiments of this scheme will not be analyzed here, and the corresponding content will be expanded in the following text.

[0050] S120: Continue to deposit aluminum nitride on the semi-finished product using the first physical vapor deposition process to obtain a finished aluminum nitride film.

[0051] In the embodiment of the present disclosure, the first physical vapor deposition process may be the process used in the above-mentioned preparation of the aluminum nitride thin film semi-finished product, but the process parameters in the first physical vapor deposition process are different from the process parameters of the above-mentioned example deposition process.

[0052] Specifically, the volume flow ratio of nitrogen to argon in the first physical vapor deposition process is much larger than that of the existing process. Specifically, in some embodiments of the present disclosure, the volume flow ratio of nitrogen to argon in the first physical vapor deposition process is greater than 95:5.

[0053] Figure 2 It is a microscopic schematic diagram of the surface of the aluminum nitride film formed in the prior art solution; Figure 3 This is a microscopic diagram of the surface of an aluminum nitride film formed by the process of the embodiment of the present disclosure. Through experimental testing, in the vapor deposition process using nitrogen and argon with a large volume flow ratio, the surface of the aluminum nitride film presents a uniform flocculent structure ( Figure 3 The structure shown in the figure is obviously different from the existing flaky mixed structure of aluminum nitride surface ( Figure 2 The structure shown in Figure 1). Because the surface structure of aluminum nitride is more uniform, it is easier to recrystallize the epitaxial layer (such as gallium nitride epitaxy) during subsequent epitaxial layer growth, reducing epitaxial growth dislocations and stress, and improving the quality of the epitaxial layer. When the quality of the epitaxial layer is improved, the thickness of the epitaxial layer can be better controlled and reduced.

[0054] Figure 4 This is a thickness simulation diagram obtained by measuring the aluminum nitride film formed according to the process of this embodiment based on an ellipsometer. Figure 5 It is a thickness simulation diagram obtained by measuring the aluminum nitride film formed based on the existing process using an ellipsometer. Figure 4 and Figure 5 Different grayscale color areas represent different thickness features. Both show the thickness of aluminum nitride film at the same magnification dimension. Figure 4 and Figure 5 It can be seen that the thickness uniformity of the aluminum nitride film obtained by the process of the embodiment of the present disclosure is significantly improved compared with the thickness uniformity of the aluminum nitride film formed by the existing process.

[0055] Figure 6 It is a distribution diagram of the diffraction light intensity in the lattice direction of the aluminum nitride film 002 formed based on the process of the disclosed embodiment. Figure 7 This is a diagram of the diffraction intensity distribution of the aluminum nitride film 102 in the lattice direction formed by the method of the embodiment of the present disclosure. Figure 6 and Figure 7 The full width at half maximum of the flocculent structure aluminum nitride film surface in the 002 lattice direction is 0.025 degrees, indicating that the uniformity quality of the aluminum nitride film lattice is obviously at an excellent level.

[0056] Based on the above-mentioned experiments combined with theoretical analysis, the above-mentioned process method is adopted. Because when the first physical deposition process is used to deposit the aluminum nitride film, the sputtered aluminum atoms combine with nitrogen atoms to form tiny grains before being deposited on the aluminum nitride film. The aforementioned tiny grains are uniformly deposited on the surface of the aluminum nitride film, so that the surface of the aluminum nitride film presents a uniform flocculent structure.

[0057] As mentioned above, in the embodiment of the present disclosure, the volume flow ratio of nitrogen to argon in the first physical vapor deposition process is greater than 95: 5. In some specific applications, the volume flow ratio of nitrogen to argon in the first physical vapor deposition process is preferably set between 95: 5 and 99: 1, preferably set to 95: 5.

[0058] As analyzed above, the reasonable use of the first physical vapor deposition process can form an aluminum nitride film with a uniform flocculent structure. However, using the first physical vapor deposition process for too long will cause the aluminum nitride film to introduce other lattice defects, resulting in a decrease in the quality of subsequent epitaxial layer growth. If the time is too short, it will cause poor surface uniformity, which is not conducive to the uniformity of subsequent recrystallization. Considering the above problems, when the first physical vapor deposition process is used to continue to deposit aluminum nitride on the aluminum nitride film semi-finished product, the duration of the first physical vapor deposition process needs to be reasonably set, specifically, the duration of the sputtering of the aluminum target material controlled by the first physical vapor deposition process needs to be reasonably set. In some embodiments, when a certain type of magnetron sputtering equipment is used to continue to grow an aluminum nitride film, the sputtering time of the aluminum target material is between 10s and 20s.

[0059] In a specific embodiment, when the magnetron sputtering device is used to perform the first physical vapor deposition process, the substrate is a sapphire substrate, and the corresponding process parameters are: the background pressure is controlled at 1x -5x Torr, the magnetron speed is controlled at 80-100r / min, the operating power of the RF power supply is controlled at 1800-2000W, the nitrogen flow rate is between 228-266sccm, the argon flow rate is between 12-14sccm, the substrate base temperature is controlled at 650-700℃, and the magnetron sputtering duration is between 10s-20s.

[0060] As mentioned above, it is necessary to prepare a semi-finished aluminum nitride film on a substrate in S110. The following is an analysis of how to preferably prepare a semi-finished aluminum nitride film in some embodiments.

[0061] Figure 8 1 is a flow chart of a method for preparing a semi-finished aluminum nitride film provided by some embodiments. Figure 8 As shown, in some embodiments, the method for preparing the semi-finished aluminum nitride thin film includes S210-S230.

[0062] S210: depositing an aluminum nitride film on a substrate to obtain an aluminum nitride film with a first target thickness.

[0063] In a specific implementation, the first target thickness is to ensure that the aluminum nitride has entered the two-dimensional structure growth stage and can form a film layer. The first target thickness is preferably 5-30 nm.

[0064] In a specific implementation, the existing preparation process can be used to deposit and grow aluminum nitride on the aluminum nitride film to obtain an aluminum nitride film with a first target thickness.

[0065] S220: performing a hydrolysis treatment on the aluminum nitride film having a first target thickness, and performing a cleaning treatment after the hydrolysis treatment.

[0066] According to the lattice structure analysis, the lattice structure of aluminum nitride is a hexagonal close-packed lattice structure, which has a certain lattice fit with the face-centered cubic close-packed lattice structure of aluminum. When using nitrogen and argon of conventional concentrations to generate aluminum nitride film, when the nitrogen concentration is low (or the nitrogen atom concentration is low), the sputtered aluminum atoms continue to deposit on the surface of the aluminum nitride lattice, and aluminum-aluminum chemical bonds may be formed, thereby forming polycrystalline or amorphous nuclei on the inner surface of the aluminum nitride film. In the subsequent continued deposition process, the aforementioned polycrystalline or amorphous nuclei continue to grow, causing atomic growth dislocation and stress generation in the aluminum nitride film, resulting in fractures, defects or non-uniform lattice structures in the aluminum nitride film. In some areas, there may also be problems in which lattice growth is restricted and stagnant, forming a blocky structure. In view of the aforementioned problems, the embodiments of the present disclosure consider removing defects in the aluminum nitride film.

[0067] In the embodiment of the present disclosure, the purpose of performing the hydrolysis treatment on the aluminum nitride film of the first target thickness is to remove defects in the aluminum nitride film through the hydrolysis treatment.

[0068] During the hydrolysis process, the aluminum element and low-energy lattice defects in the aluminum nitride film will be hydrolyzed and removed first. Of course, the aluminum nitride crystals will also be hydrolyzed by the solution. In order to avoid excessive hydrolysis of the aluminum nitride crystals themselves, the concentration, hydrolysis time and hydrolysis temperature of the hydrolysis solution need to be reasonably set.

[0069] Because the hydrolysis treatment will introduce impurities on the surface of the aluminum nitride film, and the impurities will affect the quality of subsequent film generation, it is necessary to use a reasonable hydrolysis solution and perform a cleaning treatment to remove the hydrolysis solution or hydrolysis solute.

[0070] In some embodiments of the present disclosure, a carbonic acid solution is used to hydrolyze an aluminum nitride film of a first target thickness, and corresponding S220 includes the following S221-S222.

[0071] S221: At a first target temperature, using a saturated carbonic acid solution to pickle the aluminum nitride film of a first target thickness for 600-800 seconds, the first target temperature being between 20-30°C.

[0072] In the specific implementation, the aluminum nitride film is hydrolyzed with a saturated carbonic acid solution in order to maintain the carbonic acid solution at a reasonable pH value, and the pickling temperature is controlled to maintain the first target temperature in order to reasonably control the hydrolysis reaction rate of the carbonic acid solution and the nitride film. The aluminum nitride film of the first target thickness is hydrolyzed for 600s-800s to remove the lattice defects in the aluminum nitride film as much as possible while minimizing the damage to the aluminum nitride crystal structure.

[0073] S222: performing oxygen isolation and drying treatment after the hydrolysis treatment.

[0074] In some embodiments, the film may be dried in an oxygen-free environment at a temperature of 80-100° C. for about 360 seconds to remove moisture and carbonate solutes from the surface of the aluminum nitride film.

[0075] Since carbonic acid can be decomposed into carbon dioxide and water at a certain drying temperature, and carbon dioxide and water will volatilize and will not be deposited on the surface of the aluminum nitride film, resulting in a high-cleanliness surface after subsequent drying treatment, the aluminum nitride film is hydrolyzed with a carbonic acid solution in the embodiment of the present disclosure, and the carbonic acid solute and water are removed by drying after the hydrolysis treatment. In other embodiments, other types of pickling solutions can also be used to hydrolyze the aluminum nitride film of the first target thickness. In this case, the film after pickling needs to be cleaned with deionized water and then dried to ensure the cleanliness of the aluminum nitride film surface.

[0076] S230: using a second physical vapor deposition process to continue depositing aluminum nitride on the cleaned aluminum nitride film to obtain a semi-finished product.

[0077] As analyzed above, the hydrolysis treatment can remove the lattice defects formed by the aluminum-aluminum combination in the aluminum nitride film of the first target thickness, and correspondingly, pits will be formed on the surface or inside of the aluminum nitride film after the hydrolysis treatment. The aforementioned pits have a negative impact on the subsequent uniformity of the surface of the finished aluminum nitride film. In order to solve the aforementioned problem and further increase the thickness of the aluminum nitride film, some embodiments continue to deposit aluminum nitride on the surface of the aluminum nitride film after the cleaning treatment to obtain the aforementioned semi-finished product.

[0078] In a specific implementation, the second physical vapor deposition process is used to continue to deposit aluminum nitride on the aluminum nitride film. In some specific implementations, the substrate is a sapphire substrate, and the vapor deposition equipment used in the second physical vapor deposition process is a certain type of magnetron sputtering machine. The corresponding vapor deposition process parameters are: the background pressure is controlled at 1x -5x Torr, the magnetron speed is controlled at 80-100r / min, the output power of the RF power supply is 1400-1600W, the nitrogen flow rate is 170-190sccm, the argon flow rate is 170-190sccm, the substrate base temperature is controlled at 650-700℃, the distance between the aluminum target and the substrate is 4.3-4.5cm, and the sputtering time of the aluminum target is 15-45s. The above-mentioned preparation process can make the aluminum nitride compound tend to combine with the substrate atoms, repair the pits formed after the defects are removed by hydrolysis, and continue to make the aluminum nitride grow on the substrate in a two-dimensional layered structure to form a semi-finished aluminum nitride film. At this time, the uniformity of the aluminum nitride film and the surface quality of the film layer have reached a good level.

[0079] As analyzed in the previous paragraph, the flow volume ratio of nitrogen and argon in the second physical vapor deposition process is about 1:1, which is consistent with the parameter setting in the conventional aluminum nitride film preparation process (specifically, making the ratio of aluminum atoms to nitrogen atoms an ideal stoichiometric ratio of 1:1).

[0080] According to the existing thin film preparation theory, the higher the lattice quality obtained in the previous preparation process, the smaller the impact on the subsequent process. In this solution, the fewer lattice defects generated in the previous process, the smaller the corresponding subsequent aluminum nitride lattice defects. To achieve the above-mentioned goal, in some embodiments, before executing the above-mentioned S210, the following S240 can also be executed.

[0081] S240: performing surface modification treatment on the substrate to convert surface dangling bonds of the substrate used for depositing aluminum nitride thin film into hydrogen bonds.

[0082] As analyzed above, in the preparation process of aluminum nitride film, increasing the nitrogen-aluminum ratio can reduce the aluminum-aluminum chemical bonding, thereby reducing the defects in the aluminum nitride film. If too much nitrogen is introduced in the early stage of preparation, it will cause poisoning of the aluminum target and affect the quality of the aluminum nitride film.

[0083] In order to fully increase the nitrogen-aluminum ratio and reduce the problem of aluminum target poisoning caused by increasing the nitrogen ratio in the vapor deposition process, the disclosed embodiment considers modifying the substrate surface to change the dangling bonds on the substrate surface into ammonia bonds, and providing nitrogen atoms through ammonia bonds (of course, in the subsequent high-temperature process, the chemical bonds between hydrogen atoms and nitrogen atoms are destroyed), at least to achieve the formation of aluminum nitride crystals with stable quality in the initial stage of aluminum nitride film deposition (it can be determined later that it is more about forming three-dimensional island crystal nuclei of aluminum nitride with stable quality). In addition, in the early stage of sputtering growth of aluminum nitride film, it is inevitable that there will be an amorphous layer at the bottom. The thickness of the amorphous layer is related to the oxygen content, and the original dangling bonds (aluminum bonds and oxygen bonds) have a strong affinity with oxygen atoms in the chamber. The point defects formed by oxygen atoms will recombine with nitrogen vacancies and aluminum vacancies to form an amorphous layer, which affects the film quality and the subsequent atomic diffusion, resulting in poor film uniformity. After the dangling bonds are modified into amino bonds, the affinity between the nitrogen atoms and oxygen atoms on the surface is weaker, which can well control the growth of the amorphous layer and even inhibit its growth.

[0084] In a specific implementation, the surface modification treatment of the substrate may specifically include the following S241-S242.

[0085] S241: The substrate is cleaned for 750-900 seconds at the second target temperature using an RCA solution to achieve surface modification of the substrate.

[0086] The RCA solution used in the embodiment of the present disclosure may be a mixture of ammonia water, hydrogen peroxide and deionized water. In one embodiment, the ratio of ammonia water, hydrogen peroxide and deionized water in the RCA solution may be 2:3:5.

[0087] Under the heating conditions of the RCA solution, the ammonia molecule has a lone pair of electrons and can form coordination with the aluminum atoms of the substrate (in the specific implementation, the substrate is mostly sapphire, and the surface of the sapphire is aluminum atoms). The ammonia molecule can form a coordination bond with the aluminum atoms on the surface of the sapphire through the lone pair of electrons of its nitrogen atom. This process involves the interaction between the ammonia atoms of ammonia and the electron holes of aluminum to form a stronger coordination bond. The dangling aluminum bonds on the surface are changed to ammonia bonds. In addition, under the heating conditions of the RCA solution, ammonia ions interact with the surface oxygen atoms. Because ammonia ions have positive charges, they are adsorbed near the oxygen atoms on the surface of the sapphire through van der Waals forces and interact with the oxygen atoms, so that the dangling oxygen bonds on the surface are changed to ammonia bonds.

[0088] S242: The surface-modified substrate is rinsed and oxygen-isolated and dried.

[0089] After the substrate is surface-modified with RCA solution, residual solution and corresponding solute will remain on the surface of the substrate. In order to prevent the aforementioned residual solution or solute from affecting the subsequent aluminum nitride formation, the substrate after surface modification needs to be rinsed with deionized water and oxygen-isolated drying. The aforementioned oxygen-isolated drying is to prevent the oxygen from being oxidized to form an oxide layer by the amine bond between the oxygen and the substrate, which affects the growth of aluminum nitride.

[0090] Corresponding to the operation content of the aforementioned S240, the aforementioned S210 is specifically to deposit aluminum nitride on the substrate that has undergone a modification process (specifically, a sample drying process). The corresponding S210 may include the following S211-S212.

[0091] S211: using a third physical vapor deposition process to deposit discrete aluminum nitride crystal nuclei on the modified substrate, and growing a two-dimensional layered structure based on the aluminum nitride crystal nuclei to obtain an aluminum nitride film of a second target thickness.

[0092] According to existing theories, the film formation process of aluminum nitride on the substrate needs to go through adsorption, surface migration and condensation nucleation processes. In the early stage of the vapor deposition process, when nitrogen atoms and aluminum atoms are incident on the substrate as gas phase atoms, some of them exchange energy with the substrate surface and are adsorbed on the substrate, and some of them are directly reflected back by the substrate because they do not exchange energy with the substrate surface. A very small number of gas phase atoms adsorbed on the substrate surface are evaporated again due to their high energy and detached from the substrate surface. After the remaining gas phase atoms incident on the substrate surface are adsorbed, they lose the kinetic energy along the normal direction of the substrate, but still have a certain kinetic energy parallel to the substrate surface, so the gas phase atoms can use this kinetic energy to migrate along the substrate surface and reach the area with lower surface potential energy. The atoms migrating along the surface will collide with each other and combine into atomic clusters, which condense on the substrate surface. Other migrating atoms will continue to collide and combine with these atomic clusters. In the process of colliding and combining with other atoms, the atomic clusters grow along a specific direction to form stable atomic clusters. When the number of atoms in the stable atomic clusters exceeds a certain number, stable crystal nuclei are formed. As the nuclei grow larger, they gradually merge into a film.

[0093] In some embodiments of the present disclosure, in order to cooperate with the aforementioned surface modification process to better form aluminum nitride nuclei on the substrate and form an aluminum nitride film of the second target thickness, a third physical vapor deposition process is used to deposit aluminum nitride on the substrate. The volume flow ratio of nitrogen and argon in the third physical vapor deposition process can be the same as the volume flow ratio used in the second physical vapor deposition process. However, the sputtering power per unit area of ​​the aluminum target in the third physical vapor deposition process is greater than the sputtering power per unit area of ​​the aluminum target in the second physical vapor deposition process, so that more aluminum atoms can be sputtered and the migration ability of aluminum atoms is improved.

[0094] In some embodiments, the substrate is a sapphire substrate. In order to improve the diffusion of aluminum atoms and nitrogen atoms on the substrate surface, so that aluminum nitride nuclei can grow uniformly on the substrate, and to provide a guarantee for the uniformity and film quality of subsequent aluminum nitride nuclei film formation, the first target temperature of the substrate base set in the third physical vapor deposition process is greater than the second target temperature of the substrate base in the second physical vapor deposition process. The first target temperature is set higher, which can make the diffusion ability of aluminum atoms stronger before deposition, and thus obtain a uniform distribution of nuclei. The second target temperature is set relatively low, considering the wettability of the deposition premise during the deposition process, so that the growth of aluminum nitride is converted from nucleus growth to two-dimensional growth. For example, in some specific applications, the process parameters of the third physical vapor deposition process are: the background pressure is controlled at 1x -5x Torr, the magnetron speed is controlled at 80-100r / min, the RF power is 1600-2000W, the nitrogen flow rate is controlled at 150-170sccm, the argon flow rate is controlled at 150-170sccm, the substrate base temperature is controlled at 700-800°C, and the distance between the aluminum target and the substrate is controlled at 4.3-4.5cm. In a specific implementation, by using the aforementioned process parameters to control the sputtering time for 6-10s, the aluminum nitride film can be controlled to 3-5nm, that is, the second target thickness is controlled to 3-5nm.

[0095] S212: Continue to deposit aluminum nitride on the aluminum nitride film of the second target thickness by using a second physical vapor deposition process to obtain an aluminum nitride film of the first target thickness.

[0096] After the aluminum nitride film of the second target thickness is formed by the third physical vapor deposition process, the aluminum nitride film may be further deposited on the aluminum nitride film by the second physical vapor deposition process to obtain an aluminum nitride film with a thickness of 5-30 nm.

[0097] After the aluminum nitride film of the first target thickness is obtained, it is cooled and then the hydrolysis treatment operation can be performed using the above-mentioned S220.

[0098] It should be noted that when the aforementioned physical vapor deposition process is used for thin film deposition, in order to prevent the impurities on the surface of the aluminum target from affecting the quality of aluminum nitride film formation, if the vapor deposition equipment is turned on, the aluminum target needs to be cleaned. In a specific implementation, when the vapor deposition equipment is a magnetron sputtering equipment, the RF power supply can be set at 1200W, and argon gas can be introduced to sputter and clean the surface of the aluminum target for 20s.

[0099] In order to more clearly understand the preferred embodiment of this solution, the preparation method of the aluminum nitride film in a specific embodiment is further analyzed below. Figure 81 is a flow chart of a method for preparing an aluminum nitride film provided in some embodiments of the present disclosure. Figure 8 As shown, the method for preparing the aluminum nitride film includes the following S310-S360. The process parameters used in each step correspond to the process parameters of the corresponding process in the above text, and the process effects of each process are also analyzed in the above text.

[0100] S310: performing surface modification treatment on the substrate to convert surface dangling bonds of the substrate used for depositing aluminum nitride thin film into hydrogen bonds.

[0101] S320: using a third physical vapor deposition process to deposit discrete aluminum nitride crystal nuclei on the modified substrate, and growing a two-dimensional layered structure based on the aluminum nitride crystal nuclei to obtain an aluminum nitride film of a second target thickness.

[0102] S330: Continue to deposit aluminum nitride on the aluminum nitride film of the second target thickness by using a second physical vapor deposition process to obtain an aluminum nitride film of the first target thickness.

[0103] S340: performing a hydrolysis treatment on the aluminum nitride film having a first target thickness, and performing a cleaning treatment after the hydrolysis treatment.

[0104] S350: using a second physical vapor deposition process to continue depositing aluminum nitride on the cleaned aluminum nitride film to obtain a semi-finished product.

[0105] S360: Continue to deposit aluminum nitride on the semi-finished product using the first physical vapor deposition process to obtain a finished aluminum nitride film.

[0106] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0107] The above are only specific embodiments of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to these embodiments herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an aluminum nitride thin film, characterized in that: include: Preparing an aluminum nitride film of a target thickness on a substrate, comprising: depositing aluminum nitride on the substrate to obtain an aluminum nitride film of a first target thickness; performing defect hydrolysis treatment on the aluminum nitride film of the first target thickness, and performing a cleaning treatment after the hydrolysis treatment; wherein the hydrolysis treatment is used to remove lattice defects in the aluminum nitride film, and the cleaning treatment is used to remove hydrolysis solution and / or hydrolysis solute remaining on the aluminum nitride film; and, using a second physical vapor deposition process to continue to deposit aluminum nitride on the aluminum nitride film after the cleaning treatment to obtain the aluminum nitride film of the target thickness; A first physical vapor deposition process is used to continuously deposit aluminum nitride on the aluminum nitride film of the target thickness to obtain a finished aluminum nitride film; in the first physical vapor deposition process, the volume flow ratio of nitrogen and argon is greater than 95:5 while always maintaining argon gas inlet; the first physical vapor deposition process is used to allow aluminum atoms sputtered from an aluminum target to combine with nitrogen atoms to form tiny grains before being deposited on the aluminum nitride film of the target thickness, and to allow the tiny grains to be deposited on the aluminum nitride film of the target thickness to form the finished aluminum nitride film.

2. The preparation method according to claim 1, characterized in that: The volume ratio of nitrogen to argon in the first physical vapor deposition process is greater than 95:5, specifically: The flow volume ratio of nitrogen gas to argon gas in the first physical vapor deposition process is between 95:5 and 99:

1.

3. The preparation method according to claim 1 or 2, characterized in that: The method of continuously depositing aluminum nitride on the aluminum nitride film of target thickness by using the first physical vapor deposition process comprises: The first physical vapor deposition process is controlled to last for 10-20 seconds to achieve continuous deposition of aluminum nitride on the aluminum nitride film with the target thickness.

4. The preparation method according to claim 1 or 2, characterized in that: The method of preparing an aluminum nitride film on a substrate comprises: The first target thickness is 5.0-30.0 nm.

5. The preparation method according to claim 4, characterized in that: The aluminum nitride film having a first target thickness is subjected to a hydrolysis treatment, comprising: At a first target temperature, using a saturated carbonic acid solution to hydrolyze an aluminum nitride film of a first target thickness for 600-800 seconds, wherein the first target temperature is between 20° C. and 30° C.; The cleaning treatment after the hydrolysis treatment includes: performing oxygen isolation and drying treatment after the hydrolysis treatment.

6. The preparation method according to claim 4, characterized in that: The volume flow ratio of nitrogen gas to argon gas in the second physical vapor deposition process is 1:

1.

7. The preparation method according to claim 4, characterized in that: Before the aluminum nitride is deposited on the substrate to obtain the aluminum nitride film of the first target thickness, the method further includes: performing surface modification treatment on the substrate to convert the surface dangling bonds of the substrate used for depositing the aluminum nitride film into amino bonds; The method of depositing aluminum nitride on a substrate to obtain an aluminum nitride film of a first target thickness comprises: depositing aluminum nitride on a modified substrate to obtain an aluminum nitride film of a first target thickness.

8. The preparation method according to claim 7, characterized in that: The surface modification treatment of the substrate comprises: The substrate is cleaned for 750-900 seconds at the second target temperature using an RCA solution to modify the surface of the substrate; the ratio of ammonia water, hydrogen peroxide and deionized water in the RCA solution is 2:3:5, and the second target temperature is between 80-95° C.; The surface-modified substrate is rinsed and oxygen-isolated and dried; The step of depositing aluminum nitride on the modified substrate comprises: depositing aluminum nitride on the substrate that has been subjected to oxygen isolation and drying treatment.

9. The preparation method according to claim 7, characterized in that: The step of depositing aluminum nitride on the modified substrate to obtain an aluminum nitride film with a first target thickness comprises: A third physical vapor deposition process is used to deposit aluminum nitride crystal nuclei on the modified substrate, and a two-dimensional layered structure is grown on the basis of the aluminum nitride crystal nuclei to obtain an aluminum nitride film with a second target thickness, wherein the second target thickness is 3.0-5.0 nm; Using a second physical vapor deposition process to continue depositing aluminum nitride on the aluminum nitride film of the second target thickness to obtain an aluminum nitride film of the first target thickness; Among them, the volume flow ratio of nitrogen and argon in the third physical vapor deposition process is 1:1, the gas flow rate per unit time in the third physical vapor deposition process is smaller than the gas flow rate per unit time in the second physical vapor deposition process, and the sputtering power per unit area of ​​the aluminum target in the third physical vapor deposition process is greater than the sputtering power per unit area of ​​the aluminum target in the second physical vapor deposition process.

10. The preparation method according to claim 9, characterized in that: During the aluminum nitride deposition process using the second physical vapor deposition process, controlling the substrate pedestal temperature to be a first target temperature; During aluminum nitride deposition using the third physical vapor deposition process, the temperature of the substrate base is controlled to be at a second target temperature; the first target temperature is lower than the second target temperature.